اتجاهات طلبة دبلوم التأهيل التربوي نحو المساكنة "دراسة ميدانية على طلبة التعليم المفتوح في جامعة تشرين" - عمران, هاني; عقيل, ممدوح; علي, ردينه (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
تُعدّ قضايا الشباب من الموضوعات الهامة التي يهتم بها علماء النفس والاجتماع والتربية والاقتصاد، ويُعدّ الزواج وقضايا الأسرة من أهم القضايا التي تتعلق بالشباب. ونتيجة للانفتاح الإعلامي الذي يشهده المجتمع باتت كثير من الأنماط الغربية الغريبة عن مجتمعنا تتسرب إلى الحياة الاجتماعية لأفراده ومنها المساكنة التي عُرّفت بأنها "عيش رجل وامرأة في منزل واحد دون وجود رابط شرعي بينهما". من هنا كان لا بد من دراسة اتجاهات شريحة من الشباب لمعرفة مدى تقبّلهم لمثل هذه العلاقات وأسباب انتشارها لما لها من مخاطر على استقرار الأسرة والمجتمع. تم طرح مجموعة من التساؤلات البحثية في إطار البحث الحالي وهي: 1. هل يوجد أثر للخصائص الذاتية للطلبة في اتجاهاتهم نحو قبول المساكنة؟ 2. ما هو أثر الخصائص الذاتية للطلبة في اتجاهاتهم نحو الإعلام وكافة العوامل التي تساعد على انتشار المساكنة؟ 3. ما هو أثر الخصائص الذاتية للطلبة في اتجاهاتهم نحو النتائج (السلبية والإيجابية) المتوقعة لانتشار المساكنة؟ شكّل طلبة دبلوم التأهيل التربوي في جامعة تشرين في محافظة اللاذقية بكلياتها وفروعها المختلفة للعام الدراسي 2012- 2013 مجتمع البحث وتم اختيار عينة البحث على أساس العينة العشوائية الطبقية النسبية. شخّص البحث ظاهرة المُساكنة وحلّلها للتعرف على اتجاهات الطلبة نحوها وتمّ تصميم مقياس لهذا الغرض وفق طريقة ليكرت، وتمّ تحليل البيانات باستخدام برنامج SPSS للتوصل إلى نتائج البحث. Issues of interest to the young are important topics for psychologists, sociologists, education specialists and economists. Marriage and family issues are the most important issues with which the young are concerned. As a result of media openness many alien Western life styles creep into our community as reflected in the social life of its members. Cohabitation, which is defined as "a man and a woman living in one house without a legitimate bond between them", is a case in point. Consequently, it was necessary to examine such trend among the young people to study their acceptance of such relationships which pose grave risks to family and society. This research poses the following questions: Is there a trace of students' personal characteristics in their attitudes toward acceptance of cohabitation? What is the effect of the students' personal characteristics in their attitudes toward the media and all the factors that help to spread cohabitation? What is the effect of the students' personal characteristics in their attitudes towards the results (positive and negative) of the proliferation of cohabitation? The research was conducted on astratified random sample of Educational Diploma students in various departments and faculties at Tishreen University in Lattakia during the academic year 2012-2013. The research studied and analyzed the phenomenon in order see students' attitude toward it A Likart's standard method was designed for this purpose. Data was analyzed using SPSS to get research results.